Analysis of the molecular and biochemical mechanisms involved in the symbiotic relationship between Arbuscular mycorrhiza fungi and Manihot esculenta Crantz - Gao, Yu; Huang, Siyuan; Wang, Yujie; Lin, Hongxin; Pan, Zhiyong; Zhang, Shubao; Zhang, Jie; Wang, Wenquan; Cheng, Shanhan; Chen, Yinhua (Frontiers in Plant Science, 2023)
: Plants and arbuscular mycorrhizal fungi (AMF) mutualistic interactions are essential for sus-tainable agriculture production. Although it is shown that AMF inoculation improves cassava physiological performances and yield traits, the molecular mechanisms involved in AM symbi-osis remain largely unknown. Herein, we integrated metabolomics and transcriptomics analyses of symbiotic (Ri) and asymbiotic (CK) cassava roots and explored AM-induced biochemical and transcriptional changes. Three weeks (3w) after AMF inoculations, arbuscules were formed, and plant height and root length were significantly increased. In total, we identified 1,016 metabo-lites, of which 25 were differentially accumulated (DAMs) at 3w. The most highly induced me-tabolites were 5-aminolevulinic acid, L-glutamic acid, and lysoPC 18:2. Transcriptome analysis identified 693 and 6,481 differentially expressed genes (DEGs) in the comparison between CK against Ri at 3w and 6w, respectively. Functional enrichment analyses of DAMs and DEGs un-veiled transport, amino acids and sugar metabolisms, biosynthesis of secondary metabolites, plant hormone signal transduction, phenylpropanoid biosynthesis, and plant-pathogen interac-tions as the most differentially regulated pathways. Potential candidate genes, including nitro-gen and phosphate transporters, transcription factors, phytohormone, sugar metabolism-related, and SYM (symbiosis) signaling pathway-related, were identified for future functional studies. Our results provide molecular insights into AM symbiosis and valuable resources for improving cassava production.